Augmented Reality Pengenalan Huruf dan Angka Arab Menggunakan Metode Marker Based Tracking Berbasis Android - Maurizka Zahra Devita; Septi Andryana; Deny Hidayatullah (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Hijaiyah letters are Arabic letters that are in the Koran which are studied by Muslims. Number of Hijaiyah Letters which are generally known to total 30 letters. This study aims to provide an introduction hijaiyah letters, Arabic numerals and alphabets on android smartphone by applying Augmented Reality with the media guide as a marker emergence marker object so that learning becomes more attractive. From previous research, things that have been discussed are only introduces the application Augemented Reality hijaiyah and Alphabet letters using a media card with a distance of 30 cm recommendations and recommendations 600-900 corner. This application is built using the Unity 3D, Vuforia SDK with FAST Corner Detection algorithm and 3D objects created using Blender. This application uses the marker method used to determine the point of emergence of 3D objects. The results of validation testing concluded if all valid system. Testing algorithms with the point x1, y1, x2 and y2, condition of the camera to the marker on the distance is 50 cm at an angle of 450 and a distance of 50 cm - 60 cm at an angle of 900.